PENGARUH KOMPENSASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA BANK SYARIAH INDONESIA CABANG BINTARO - Edi Purwanto; Imam Muhtadin; Vira Pingky Lestari (Media Riset Bisnis Ekonomi Sains dan Terapan, 2023)
This study aims to analyze the influence on independent variables of Compensation and Job Stress on Employee Performance as the dependent variable. Data analysis uses multiple linear test, determination coefficient and hypothesis test. Analysis in this study using SPSS. V. 22. The results of this study indicate that the Compensation variable has a positive and significant effect on Employee Performance based on the results of the statistical test t test shows that the results between t count t table (4.102 1.705) with a significant value Compensation of 0.000 is smaller than 0.05 and has a direction positive coefficient. The perception of work stress has a positive and insignificant effect on employee performance with the results of the tt test t table (0.321 1.705) with a significant value of the Competency variable of 0.751 greater than 0.05 and has a direction positive coefficient. The results of the f test Compensation and Work Stress together (simultaneously) have a positive and significant effect between f count f table ((7.656 3.35) with a significant value of 0.003 smaller than 0.005 or 5%.